Taxation and Accounting Data Management: An Empirical Study in Cameroon (Global Journal of Management and Business Research, 2022)
This paper analyses the relationship between taxation and accounting data management in the Cameroonian context based on a sample of 1474 firms in the period 2014-2017 This link is estimated using a simultaneous equation model which allows us to highlight the reciprocal influence between the two variables The results show that fiscal pressure has a positive two-way effect on discretionary accruals although this relationship is negative in large companies The findings also show a non-linear relationship between discretionary accruals and effective tax rate It is concave in small and medium-size enterprises That is at low levels of effective tax rate the relationship is positive it becomes negative at higher levels Conversely it assumes a U-shape form in large companies meaning that at low levels of effective tax rate the relationship is negative becoming positive at higher levels
Keywords: taxation; accounting data management; discretionary accruals; effective tax rate